Cytokine-Induced Killer Cells As Pharmacological Tools for Cancer Immunotherapy - Gao, Xingchun; Mi, Yajing; Guo, Na; Xu, Hao; Xu, Lixian; Gou, Xingchun; Jin, Weilin (Frontiers in Immunology, 2017)
Cytokine-induced killer (CIK) cells are a heterogeneous population of effector CD3+CD56+ NKT cells which can be easily expanded in vitro from peripheral blood mononuclear cells (PBMC). CIK cells work as pharmacological tools for cancer immunotherapy as they exhibit MHC-unrestricted, safe and effective anti-tumor activity. Much effort has been made to improve CIK cells cytotoxicity and treatments of CIK cells combined with other anti-tumor therapies are applied. This review summarizes some strategies, including the combination of CIK with additional cytokines, DC cells, check point inhibitors, antibodies, chemotherapeutic agents, nanomedicines, and engineering CIK cells with a CAR (chimeric antigen receptor). Furthermore, we briefly sum up the clinical trials on CIK cells and compare the effect of clinical CIK therapy with other immunotherapies. Finally, further research is needed to clarify the pharmacological mechanism of CIK and provide evidence to formulate uniform culturing criteria for CIK expansion.